2013
DOI: 10.1007/s00705-013-1730-7
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of a novel potato virus S strain infecting Solanum phureja in Colombia

Abstract: Potato virus S (PVS) (genus Carlavirus, family Betaflexiviridae) is one of the most prevalent viruses in potato crops (Solanum tuberosum and S. phureja) around the world, causing reductions in crop yields between 10 and 20 %. Symptoms of PVS infection may include leaf mottling, rugosity of leaves, deepening of the veins and reductions in crop yields between 10 and 20 %. Virions are flexuous rods of 610-710 nm with a positive-sense ssRNA genome of approximately 8500 nt comprising six ORFs, a 5'CAP and a 3'poly-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 13 publications
0
9
0
3
Order By: Relevance
“…These are crops from such diverse species that it is likely many wild hosts may also be infected constituting a continual environmental reservoir for these viruses present in the absence of cultivated plant hosts. In addition, the viruses commonly found in other parts of the world often show much higher level of variability in the Andean region (Gil et al 2016a, b;Kalyandurg et al 2017;Santillan et al 2018;Gutierrez et al 2013;Gibbs et al 2017;Henao-Díaz et al 2013).…”
Section: Viruses In the Andean Regionmentioning
confidence: 99%
“…These are crops from such diverse species that it is likely many wild hosts may also be infected constituting a continual environmental reservoir for these viruses present in the absence of cultivated plant hosts. In addition, the viruses commonly found in other parts of the world often show much higher level of variability in the Andean region (Gil et al 2016a, b;Kalyandurg et al 2017;Santillan et al 2018;Gutierrez et al 2013;Gibbs et al 2017;Henao-Díaz et al 2013).…”
Section: Viruses In the Andean Regionmentioning
confidence: 99%
“…It was later shown to be an isolate of PVS-A (Kobayashi et al, 1985). Similarly, Gutierrez et al (2013) reported a novel PVS isolate (PVS-RVC) in S. phureja, a tuber-forming Solanum species grown in the Andes region. Vallejo et al (2016) reported a related PVS isolate in the same host.…”
Section: Intraspecific Diversitymentioning
confidence: 94%
“…La situación encontrada para la detección del virus PVS fue contraria a lo antes expuesto, pues el virus se encontró mediante ELISA en el 80,5 % de las muestras y tan sólo en el 25 % de éstas, cuando se utilizó RT-qPCR. Dicha diferencia, indica la necesidad de diseñar nuevos cebadores que cubran toda la variabilidad genética que presenta PVS en los Andes colombianos y que ha sido claramente demostrada en estudios filogenéticos recientes (Gutiérrez et al, 2012;Gutiérrez et al, 2013;Santillan et al, 2018), en donde se han encontrado al menos tres linajes diferentes para este virus: PVS A , PVS O y PVS P ; este último hasta ahora solo encontrado en Antioquia (Colombia) y denominado PVS P haciendo referencia a su detección inicial en papa criolla (S. phureja) (Vallejo et al, 2016). Ya que las secuencias de este linaje sirvieron de base para el diseño de los cebadores PVS_gen_F y qPVS_gen_R utilizados en el presente trabajo, es posible inferir que dichos cebadores presentan desajustes (mismatches) con respecto a sus regiones de unión en algunos genotipos de este virus que se encuentran infectando las muestras evaluadas; mientras que los anticuerpos empleados en las pruebas de ELISA cubren un rango mayor de variación, dada su unión con regiones muy conservadas de la proteína de la cápside de este virus.…”
Section: Figuraunclassified